Between Faith and Psychiatry: A Sociological Inquiry into the Use of Roqya for Mental Disorders - Laila El Boutahiri; Mohamed Fadil (UIN Sjech M. Djamil Djambek Bukittinggi, 2025)
This paper aims to show the relationship between cultural and religious interpretations of mental disorders and the use of spiritual healing practices. The interest of this study lies in understanding how these interpretations can guide curative choice, especially in the Moroccan context, where modern medicine coexists with traditional and religious practices. Interrogating these explanations in the hospital context, where two completely distinct conceptions may come into conflict, is an essential and novel task. Through a qualitative approach and with the use of interviews conducted with families of patients hospitalized in a psychiatric hospital in the city of Fez, this work highlights the presence of supernatural conceptions of mental disorders in the participants, such as possession, the evil eye, and witchcraft. Thus, it is evident that these conceptions have led to the adoption of a healing practice based on Koranic recitations, known as Roqya. This research is not intended to be generalized due to the small sample size; its results represent the experiences of the participants interviewed within the context of the study. However, the significance of it lies in the fact that it stresses the importance of a medical approach that is open to cultural interpretations of mental disorders and aware of their impact on patients' choices.